CD11c+CD163+ Cells and Signal Transducer and Activator of Transcription 3 (STAT3) Expression Are Common in Melanoma Leptomeningeal Disease - Najem, Hinda; Marisetty, Anantha; Horbinski, Craig; Long, James; Huse, Jason T.; Glitza Oliva, Isabella C.; Ferguson, Sherise D.; Kumthekar, Priya U.; Wainwright, Derek A.; Chen, Peiwen; Lesniak, Maciej S.; Burks, Jared K.; et al. (Frontiers in Immunology, 2021)
Leptomeningeal disease (LMD) in melanoma patients is associated with significant neurological sequela and has a dismal outcome, with survival measured typically in weeks. Despite the therapeutic benefit of targeted therapies and immunotherapies for Stage IV melanoma, patients with LMD do not typically benefit. A deeper understanding of the tumor microenvironment (TME) of LMD may provide more appropriate therapeutic selection. A retrospective analysis of subjects who underwent surgical resection with LMD (n=8) were profiled with seven color multiplex staining to evaluate the expression of the global immune suppressive hub - the signal transducer and activator of transcription 3 (STAT3) and for the presence of CD3+ T cells, CD68+ monocyte-derived cells, CD163+ immune suppressive macrophages, and CD11c+ cells [potential dendritic cells (DCs)] in association with the melanoma tumor marker S100B and DAPI for cellular nuclear identification. High-resolution cellular imaging and quantification was conducted using the Akoya Vectra Polaris. CD11c+ cells predominate in the TME (10% of total cells), along with immunosuppressive macrophages (2%). Another potential subset of DCs co-expressing CD11c+ and the CD163+ immunosuppressive marker is frequently present (8/8 of specimens, 8%). Occasional CD3+ T cells are identified, especially in the stroma of the tumor (p=0.039). pSTAT3 nuclear expression is heterogeneous in the various immune cell populations. Occasional immune cluster interactions can be seen in the stroma and on the edge. In conclusion, the TME of LMD is largely devoid of CD3+ T cells but is enriched in immune suppression and innate immunity.